In-hospital Mortality and Causes of Death in People Diagnosed With HIV in a General Hospital in Shenyang, China: A Cross-Sectional Study - Li, Cheng Bo; Zhou, Ying; Wang, Yu; Liu, Sheng; Wang, Wen; Lu, Xu; Sun, Cui Ming; Liu, Pei; Hu, Qing-Hai; Wen, Ying (Frontiers in Public Health, 2021)
Background: Acquired immune deficiency syndrome (AIDS), caused by human immunodeficiency virus (HIV) infection, is a serious public health issue. This study investigated the correlated factors and possible changing trend of in-hospital death in patients diagnosed with HIV in the past decade in our hospital. Methods: We retrospectively collected data of firstly hospitalized patients with HIV in the Department of Infectious Disease in the First Affiliated Hospital of China Medical University from January 1, 2010 to December 31, 2019, and compared various factors that correlated with in-hospital death, including age, sex, opportunistic infections, and antiretroviral therapy (ART) status. Cox regression analysis was used to identify the risk factors for death. Results: In total, 711 patients were recruited for this study, and 62 patients died in the hospital. The in-hospital mortality rate was 8.72%. Tuberculosis (TB), malignancies, and thrombocytopenia were associated with mortality. Antiviral treatment before admission was found to be a protective factor. There was a declining trend in in-hospital mortality from 19.2% in 2010 to 6.3% in 2019 (linear-by-linear association test, p<0.001), partly due to intensified medical care strategy. Conclusions: Till date, AIDS-defining illnesses remain the major cause of hospital admission and in-hospital mortality. TB and malignancies were correlated risk factors for in-hospital mortality. ART before admission was found to be beneficial, and considering the decreasing rate of in-hospital mortality, the implementation of intensified medical care strategy requires further effort.